Star child : a biographical constellation of Octavia Estelle Butler - Zoboi, Ibi Aanu (Dutton Children's Books, 2022)
Profiles the life of fantasy fiction writer Octavia Butler using a variety of verse, poems, and prose to describe her youth growing up during the Space Race, her family, and how she became dedicated to the art of science fiction writing. The author also explores her own ties to the author and Butler's influence on the author's work.